Corticospinal Tract Hypoperfusion Associated With Unexplained Early Neurological Deterioration After Intravenous Thrombolysis - Zhang, Danfeng; Zhong, Wansi; Chen, Luowei; Xu, Chao; Yan, Shenqiang; Zhou, Ying; Ma, Xiaodong; Lou, Min (Frontiers in Neurology, 2022)
Background and Purpose: Early neurological deterioration (END) occurs in 10% acute ischemic stroke (AIS) patients receiving intravenous thrombolysis (IVT), and over half of them had no straightforward causes, named as unexplained END. We aimed to explore whether the presence of baseline corticospinal tract (CST) hypoperfusion could predict the development of unexplained END at 24 hours in AIS patients after IVT. Methods: We retrospectively analyzed the clinical and imaging data from AIS patients who received IVT. Unexplained END was defined as ≥ 2-point increase of National Institutes of Health Stroke Scale (NIHSS) from baseline to 24 hours, without straightforward causes. Hypoperfusion lesions involving CST and other cerebral areas were identified on perfusion maps. Results: Of 807 patients, CST hypoperfusion and non-CST hypoperfusion occurred in 488 (60.5%) and 319 (39.5%) patients, respectively. Patients with CST hypoperfusion were more likely to have unexplained END compared with patients with non-CST hypoperfusion (16.6% vs 2.8%, P <0.001). Binary logistics regression analysis showed that CST hypoperfusion was independently associated with unexplained END after IVT (OR= 5.640; 95% CI: 2.699-11.785; P <0.001) after adjusting for baseline NIHSS, onset to needle time, baseline hypoperfusion volume, atrial fibrillation and hypertension. Conclusions: Patients with CST hypoperfusion were more likely to suffer from unexplained END after IVT, with important implications regarding underlying mechanisms and potential prevention of unexplained END.